THE EFFECT OF CELEBRITY ENDORSEMENT ON PURCHASE INTENTION WITH BRAND AWARENESS MEDIATION ON SCARLETT WHITENING IN MAKASSAR CITY - Andhani, Rima; Kurniawan, Agung Widhi; Hasdiansa, Ilma Wulansari; Riu, Isma Azis; Abadi, Rahmat Riwayat (Jurnal Manajemen, 2025)
Abstract: This study aims to analyze the effect of celebrity endorsement on consumer purchase intention with brand awareness as a mediating variable on Scarlett Whitening products in Makassar City. Celebrity endorsement is one of the most frequently used marketing strategies in the beauty industry, because it is considered capable of forming positive perceptions and attracting consumer buying interest. However, the effectiveness of this strategy can be influenced by the level of brand awareness among consumers. This study uses a quantitative approach with a survey method by distributing questionnaires to respondents who meet the criteria, namely individuals who have never purchased Scarlett Whitening products but have seen advertisements for the product featuring celebrities. The data obtained were analyzed using the Structural Equation Modeling technique based on Partial Least Square. The results of the analysis show that celebrity endorsement has a positive and significant direct influence on brand awareness and purchase intention. In addition, brand awareness is proven to have a positive and significant influence on purchase intention and also mediates the relationship between celebrity endorsement and purchase intention. These findings indicate that brand awareness plays an important role in strengthening the influence of celebrities on consumer purchase intention. Therefore, marketing strategies involving celebrities as endorsers are considered effective, especially when combined with efforts to build strong brand awareness.Keywords: Celebrity Endorsement, Brand Awareness, Purchase Intention, Scarlett Whitening, Makassar.